2019
DOI: 10.1186/s12958-019-0496-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of sperm in unexplained recurrent pregnancy loss

Abstract: Background Recurrent pregnancy loss (RPL) refers to two or more spontaneous abortions that occur consecutively with the same spouse. RPL severely affects human reproduction health, and causes extreme physical and mental suffering to patients and their families. Methods We used isobaric tags for relative and absolute quantitation (iTRAQ), which was coupled with liquid chromatography mass spectrometry (LC-MS) proteomic analysis, in order to identify differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Comparative proteomics studies have previously been conducted on sperm [ 29 , 30 , 31 ]. However, RM patients have only been included in a few recent reports [ 23 , 32 ]. To our knowledge, this is the first study that analyzes the protein profile of patients categorized as being at high risk of RM according to their sperm DNA DSB profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative proteomics studies have previously been conducted on sperm [ 29 , 30 , 31 ]. However, RM patients have only been included in a few recent reports [ 23 , 32 ]. To our knowledge, this is the first study that analyzes the protein profile of patients categorized as being at high risk of RM according to their sperm DNA DSB profile.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the advances in the search for male-factor-related biomarkers for RM, such as the presence of DSB, new molecular biomarkers need to be identified in order to better understand the physiopathology of this disease. In this sense, a study by Xue et al [ 23 ] identified 38 proteins that were significantly altered in RM patients, mostly related to metabolic processes, biological regulation, and protein binding activities [ 23 ]. Additionally, a study by Sutovsky et al [ 24 ] identified that patients with high SPTRX3 protein content in semen are prone to RM [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the iTRAQ-based proteomic technology that offers improved accuracy in terms of protein quantification was used. The methods used to screen differentially expressed proteins in the two previous studies included LC-MS/MS, two-dimensional gel electrophoresis, liquid chromatography-mass spectrometry, and matrixassisted laser desorption ionization-time-of-flight-mass spectrometry analysis; however, the iTRAQ-based technology used here is a high-throughput method used extensively for quantitative proteomic analysis of sperm [7,20,21]. Therefore, as expected, additional differentially expressed proteins that are potentially associated with infertility were discovered.…”
Section: Discussionmentioning
confidence: 99%
“…This protein has seven catalytic activities and a site for the binding of the prosthetic group 4'-phosphopantetheine of the acyl carrier protein (ACP) domain (51). Overexpression of FASN was confirmed by WB analysis in semen samples from couples with unexplained recurrent pregnancy loss (52). In somatic cells, homologous recombination (HR) is the main molecular mechanism for DSB repair, which occurs by using the sister chromatid as a template.…”
Section: Discussionmentioning
confidence: 99%